Blockchain-based Machine-to-Machine Communication in the Industry 4.0 applied at the Industrial Mining Environment - Garrocho, Charles; Klippel, Emerson; Machado, Anderson; Ferreira, Célio Márcio; Cavalcanti, Carlos Frederico; Oliveira, Ricardo Augusto (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2020: Anais do X Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2020)
The Industrial Internet of Things is expected to attract significant investments for Industry 4.0. In this new environment, blockchain have immediate potential in industrial applications, providing immutable, traceable and auditable communication. However, works on the blockchain literature targets environments that do not meet the reality and requirements of a factory, in addition to needing cloud infrastructure in which communication delay increases. In this context, this article presents a blockchain-based machine-to-machine communication architecture, which it is deployed directly to industrial devices. Evaluation results reveal the need for the evolution of the current stage of blockchain technologies to meet the strict requirements time demanded by machine-to-machine communication in the industrial mining environment.